Dietary Patterns and Risk of Chronic Kidney Disease Progression and All-Cause Mortality: Findings from the CRIC study. (29th May 2020) - Hu, Emily; Coresh, Josef; Anderson, Cheryl; Appel, Lawrence; Grams, Morgan; Crews, Deidra; Mills, Katherine; He, Jiang; Scialla, Julia; Rahman, Mahboob; Lash, James; Navaneethan, Sankar; et al.
Abstract: Objectives: Current dietary guidelines recommend that chronic kidney disease (CKD) patients reduce intake of individual nutrients, such as sodium, potassium, phosphorus, and protein. This approach can be difficult for patients to implement and ignores important nutrient interactions. Our objective was to define the association of healthy dietary patterns with risk of CKD progression and all-cause mortality among people with CKD. Methods: We analyzed data from 2403 participants aged 21–74 years with an estimated glomerular filtration rate (eGFR) of 20–70 mL/min/1.73 m 2 and dietary data in the Chronic Renal Insufficiency Cohort (CRIC) study. Healthy Eating Index-2015 (HEI-2015), Alternative Healthy Eating Index-2010 (AHEI-2010), alternate Mediterranean diet (aMed), and Dietary Approaches to Stop Hypertension (DASH) diet scores were calculated using data collected from food frequency questionnaires. We analyzed the association between these dietary patterns and two main outcomes: 1) CKD progression defined as ≥50% eGFR decline, kidney transplantation, or dialysis, and 2) all-cause mortality. Cox proportional hazards regression models adjusted for demographic, lifestyle, and clinical covariates were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). Results: There were 855 cases of CKD progression and 773 deaths over a maximum of 14 years. Compared with participants with the lowest adherence, the most highly adherent tertile of AHEI-2010, aMed, and DASH had lower adjusted risk of CKD progression with the strongest association for aMed (HR: 0.75, 95% CI: 0.62–0.90). Nuts and legumes were independently associated with lower risk of CKD progression. Compared with participants with the lowest adherence, the highest adherence tertiles for all four scores had a 24–31% lower adjusted risk of all-cause mortality. Conclusions: Greater adherence to a healthy dietary pattern is associated with a lower risk of CKD progression and all-cause mortality among people with CKD. Guidance to adopt healthy dietary patterns should be incorporated into guidelines for individuals with CKD. Funding Sources: NIH (NHLBI, NIDDK).